Avaliação do perfil das angiotensinas em pacientes cardiopatas submetidos a angioplastia percutânea - Renata da Cunha Ribeiro (2020)
Introduction: According to the Brazilian Society of Cardiology, in Brazil there is 1 death from cardiovascular causes every 90 seconds and cardiovascular disease causes twice as many deaths as those due to all types of cancer combined. Although a decrease in ischemia-related mortality has been observed in recent years and its pathophysiology has been extensively studied, there are still unanswered questions, such as the role of the new components of the Renin-Angiotensin System (RAS). Objectives: To evaluate the profile of the RAS peptides, Alamandine, Angiotensin-(1-7), Angiotensin I and Angiotensin II, in cardiac patients undergoing isolated Cardiac Catheterism or followed by Percutaneous Angioplasty because Acute Coronary Syndrome and evaluate mRNA expression of ACE2, AT1 and Mas receptors in the same group of patients. Materials and Methods: 26 patients who underwent cardiac catheterism followed or not by Percutaneous Angioplasty were recruited. The Groups were divided according the use of medication or not, hypertension or not, the result of catheterism (normal or not) and Angioplasty. In each patient, blood was collected from the peripheral vein and the aortic root. In patients who underwent Angioplasty, blood was also collected at the same locations 5 minutes after Angioplasty. Alamandine, Angiotensin-(1-7), Angiotensin I and Angiotensin II were measured in each patient using Mass Spectrometry and research for AT1, Mas and ECA2 receptor mRNA in arterial blood polymorphonuclear cells (PBMC). Results: Alamandine and Angiotensin II increase with the degree of coronary disease. Angiotensin-(1-7) has its lowest absolute value in patients undergoing Angioplasty, while Angiotensin I presents, in patients undergoing Angioplasty, an intermediate value between those who have had a result of normal and injured Catetherism. After Angioplasty, Alamandine had a predominance of pulmonary formation, while Angiotensin I and Angiotensin II had a predominance of degradation. Angiotensin-(1-7) maintained a balance between these two phenomena after Angioplasty. The conversion of Angiotensin I to Angiotensin II as well as the Angiotensin- (1-7) / Angiotensin II ratio vary according to the degree of coronary disease, the medication used by the patient and the presence or not of Hypertension. The degree of coronary disease seems to have little influence on the expression of the studied receptors and also on the AT1 / Mas ratio. Discussion: We have few studies in humans that measure the values of the studied peptides. Most studies involving patients focus on clinical outcomes and stent restenosis. Our results were different from those found in the literature due to its design and method of measuring peptides. However, our data suggests that the degree of coronary disease as well as Angioplasty affect the plasma value of circulating Angiotensis and their pulmonary processing. These changes appear to be co-influenced by the use of medications such as Beta Blockers, ACEi and ARA and also by patient’s comorbidities. In contrast, the ACE2, AT1 and Mas receptors, as well as the AT1 / Mas ratio seems to be little influenced by the factors mentioned. Conclusion: Studies on patients are expensive and difficult from an ethical point of view due to the heterogeneity of the sample, thus leading to the need for a large number of patients and/or follow-up for a long period. Despite the limitations, our data suggest that the RAS is influenced by both the degree of coronary disease and the medications used by the patient, which also influence the patient’s response to Angioplasty. The ACE2, AT1 and Mas receptors are less sensitive to the factors mentioned.